The clinical significance of vitamin D levels and vitamin D receptor mRNA expression in colorectal neoplasms. Issue 11 (15th October 2021) - Fang, Ying; Song, Haojun; Huang, Jian; Zhou, Jianbo; Ding, Xiaoyun
Abstract: Background/Aim: This study aimed to investigate the clinical significance of changes in vitamin D [25(OH)D] levels and vitamin D receptor (VDR) mRNA expression in colorectal adenoma development. Methods: Plasma concentrations of 25(OH)D and mRNA expression of VDR in tissues were determined by enzyme‐linked immunosorbent assay (ELISA) and real‐time fluorescence quantitative polymerase chain reaction (RT‐qPCR), respectively. In addition, the concentration of plasma 25(OH)D and levels of VDR mRNA in tissues were compared among healthy individuals and adenoma and adenocarcinoma patients. Results: Vitamin D receptor expression in colorectal adenocarcinoma tissues was significantly lower than that in para‐cancerous tissues that were >5 cm away from malignant tumor sites ( p < 0.01). The level of VDR expression in normal colorectal tissues from healthy individuals was significantly higher than that in colorectal adenomas ( p < 0.01) and colorectal adenocarcinomas ( p < 0.01); however, the VDR expression was not significantly different between colorectal adenomas and colorectal adenocarcinomas ( p = 0.106). The concentration of 25(OH)D in healthy individuals was significantly higher than that in patients with colorectal adenomas ( p < 0.01) and colorectal adenocarcinomas ( p < 0.01); however, the concentration of 25(OH)D was not significantly different between colorectal adenomas and colorectal adenocarcinomas ( p = 0.489). A low concentration of 25(OH)D was considered a risk factor for colorectal adenoma and colorectal adenocarcinoma, with odds ratios of 4.875 and 2.925, respectively. Conclusions: The 25(OH)D levels and VDR mRNA expression might be associated with the development of colorectal adenoma and its progression to adenocarcinoma. Abstract : The levels of 25(OH)D and VDR mRNA expression might be associated with the development of colorectal adenoma and the progression to adenocarcinoma.